EVALUATON OF NATIVE STARCH EXTRACTED FROM SORGHUM LANCEOLATUM AS TABLET DISINTEGRANT - Emenike, I. V,; Saka, L.K.,; Timothy, S.Y.,; Musa, H., (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2016)
This study aims at evaluating a tablet excipient from a local source, red guinea corn Sorghum lanceolatum starch which is used locally as food because of its high carbohydrate content. It was thought that the starch of red guinea corn Sorghum lanceolatum may serve as a tablet disintegrant. Native starch was obtained by wet method of extraction by soaking 3 kg of Sorghum lanceolatum in water with well dissolved NaOH for 24 hour. The water were decanted and followed with washing, grinding and sieving the grinded corn, then enough water was added to the filtrate, allowed to settle and the precipitant was decanted. Re-suspension, bleaching with sodium hypochlorite and sedimentation were done repeatedly and white substance obtained was centrifuged using thermo-electron machine at 1000 rev/min for 10 mins. The white starch obtained was dried at room temperature for 5 days and at 48oC for 24 hours. The result of the research shows that Mechanical properties such as weight variation, friability and crushing strength of tablets formulated with native starch were similar to those of Maize starch (Zea mays) B.P. were carried out disintegration as specified by BP. 2009, were carried out.Tablets formulated with native starch disintegrate faster compare to that formulated with Maize starch (Zea mays) B.P. disintegration time as specified by B.P 2009, was also carried out. In conclusion, native starch can be incorporated as a wet granulation excipient in the formulation of paracetamol tablets formulation.